Coupling PEDOT on Mesoporous Vanadium Nitride Arrays for Advanced Flexible All‐Solid‐State Supercapacitors. Issue 37 (9th August 2020) - Chen, Minghua; Fan, He; Zhang, Yan; Liang, Xinqi; Chen, Qingguo; Xia, Xinhui
Abstract: Tailored construction of advanced flexible supercapacitors (SCs) is of great importance to the development of high‐performance wearable modern electronics. Herein, a facile combined wet chemical method to fabricate novel mesoporous vanadium nitride (VN) composite arrays coupled with poly(3, 4‐ethylenedioxythiophene) (PEDOT) as flexible electrodes for all‐solid‐state SCs is reported. The mesoporous VN nanosheets arrays prepared by the hydrothermal–nitridation method are composed of cross‐linked nanoparticles of 10–50 nm. To enhance electrochemical stability, the VN is further coupled with electrodeposited PEDOT shell to form high‐quality VN/PEDOT flexible arrays. Benefiting from high intrinsic reactivity and enhanced structural stability, the designed VN/PEDOT flexible arrays exhibit a high specific capacitance of 226.2 F g −1 at 1 A g −1 and an excellent cycle stability with 91.5% capacity retention after 5000 cycles at 10 A g −1 . In addition, high energy/power density (48.36 Wh kg −1 at 2 A g −1 and 4 kW kg −1 at 5 A g −1 ) and notable cycling life (91.6% retention over 10 000 cycles) are also achieved in the assembled asymmetric flexible supercapacitor cell with commercial nickel–cobalt–aluminum ternary oxides cathode and VN/PEDOT anode. This research opens up a way for construction of advanced hybrid organic–inorganic electrodes for flexible energy storage. Abstract : Mesoporous vanadium nitride arrays coupled with poly(3, 4‐ethylenedioxythiophene) (PEDOT) as an integrated electrode for all‐solid‐state flexible supercapacitors show excellent cycling stability and high energy densities. High‐performance capacitive behavior is contributed by the effect of surface‐controlled process and PEDOT coating protection.